PHYTOCHEMICAL ANALYSIS, ANTIOXIDANT AND ANTIMICROBIAL ACTIVITY OF SYZYGIUM CARYOPHYLLATUM ESSENTIAL OIL - SONI, AMRITA; DAHIYA, PRAVEEN (Asian Journal of Pharmaceutical and Clinical Research, 2014)
Objective: To investigate the phytochemical constituents, TLC bioautography and antioxidants of Syzygium caryophyllatum essential oil. The antimicrobial potential was also determined against various multi drug resistant clinical isolates. Methods: Preliminary phytochemical analysis was performed. The antimicrobial potential of essential oil from Syzygium caryophyllatum was evaluated by agar well diffusion method against multi drug resistant clinical isolates. The antibacterial effect was investigated using the TLC-bioautographic method. The antioxidants analyzed include catalase, superoxide dismutase, glutathione-S-transferase and glutathione reductase. Results: Phytoconstituents analysis demonstrated the presence of alkaloids, cardiac glycosides, flavanoids, steroids, saponins and tannins. Syzygium caryophyllatum oil was further investigated for its antimicrobial activity against twelve Multi drug resistant pathogenic bacteria and four fungi respectively. The highest in vitro inhibitory activity was observed for klebsiella sp.3 with wide inhibition zone diameters (22±0.07 mm) followed by klebsiella sp.2 (17±0.12 mm) and S. aureus 2 (13±0.11 mm). Among fungal isolates, inhibitory activity was observed for Aspergillus niger, Aspergillus sp and Rhizopus nigricans. Thin layer chromatography bioautography demonstrated one large inhibitory zone with Rf value of 0.91 against the growth of isolate Klebsiella sp. 3. The oil was found to be rich in antioxidants such as superoxide dismutase, glutathione reductase and glutathione-S-transferase. Conclusion: It can be concluded that Syzygium caryophyllatum oil can be used as a potential source of natural antimicrobial compound possessing strong antioxidant potential. Key words: Syzygium caryophyllatum, antibacterial activity, antifungal activity, antioxidant potential, agar well diffusion, TLC Bioautography